Stress analysis of a compound joint for multiple tubular members using finite element method - Lim, Ching Hwa, 1986-; Mohd. Nasir Tamin, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2010